Missing Children: Kidnapped and Abducted Children and Resources Available to Parents and the Community - Stacy Daniels; Mark A. Brennan (EDIS)
FCS-2256, a 5-page fact sheet by Stacy Daniels and M.A. Brennan, is the second in a two-part series focusing on missing children. This final installment considers children who have been abducted. Readers will learn about different types of abductions (family, nonfamily, and kidnapping) and find out how common each type is. This paper also provides information on some of the resources available for families, community leaders, and extension agents and tips on how to prevent abductions in any community. Published by the UF Department of Family Youth and Community Sciences, October 2006.